2017
DOI: 10.4172/2161-0401.1000184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wastewater Treatment Plants in El-Gharbia Governorate, Egypt

Abstract: The present study has been undertaken to evaluate performance efficiency of wastewater treatment plants in El-Gharbia governorate in Egypt. The wastewater treatment plants using different biological treatment techniques (conventional activated sludge, oxidation ditch, extended aeration, rotating biological contactors and aerated lagoons processes). Wastewater samples were collected from both influent and effluent of each plant and the wastewater quality were determined at central laboratory of Garbyia Water Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The performance of both sewage treatment plants of removing COD, ammonia and fecal coliform bacteria is low, in comparison with EPA guidelines (EPA, 2012). Ramadan et al (2017) reported the low efficacy potential of some wastewater treatment plants in Gharbia governorate, especially those operated by activated sludge (the same case, as in the present study).…”
Section: Assessment Of Water Treatment Plantssupporting
confidence: 78%
“…The performance of both sewage treatment plants of removing COD, ammonia and fecal coliform bacteria is low, in comparison with EPA guidelines (EPA, 2012). Ramadan et al (2017) reported the low efficacy potential of some wastewater treatment plants in Gharbia governorate, especially those operated by activated sludge (the same case, as in the present study).…”
Section: Assessment Of Water Treatment Plantssupporting
confidence: 78%
“…Some of the several reasons for using WWTPs assessment are to test the effluent water quality with the local standards and regulations for an overall evaluation of the plant's capability for the incoming loadings and to check on different sides of the plant, like its maintenance plans and the financial budgeting to determine if it needs to be updated. A plant's evaluation is sometimes considered a means to study the future possibilities for developing the plant if it is in terms of updating the existing parts or adding new elements and plans for the plan [17]. Evaluating the plant starts by studying the design (plans and detailed drawings) of WWTPs in general and for a selected case study as a sample.…”
Section: Methodsmentioning
confidence: 99%
“…Water contamination is linked to the development of urbanization, industry, and agricultural drainage (Aboulfotoh & Heikal 2022;Ramadan et al, 2017;Benaissa et al, 2022). One of the most serious risks to surface and groundwater is contamination from sewage (Aboulfotoh & Heikal 2022; Duong et al, 2022;Rizani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%